Lake ice phenology: a comparison between TSX and Sentinel-1 images using field data analysis in a maritime Antarctica region - Viel, Jorge Antônio; Petsch, Carina; Velho, Luiz Felipe; da Rosa, Kátia Kellem (Investigaciones Geográficas: Una mirada desde el sur, 2022)
The monitoring of lake ice phenology in ice-free areas over time is relevant for understanding the impacts of global warming and extreme weather events in polar regions. The objectives of this work are: (i) to define backscatter values for ice-free and ice-covered surface water targets - which are supported by field data - as well as snow on lakes, from TerraSar-X (TSX) and Sentinel 1A - EW (S-1) images from the Fildes Peninsula, on Maritime Antarctica; (ii) to evaluate the relationship between backscatter and meteorological data; and (iii) to estimate the potentialities of TSX and S-1 for mapping lake phenology. These images were processed in SNAP, while the meteorological data were obtained from the Eduardo Frei Montalva Base. It was obtained a backscatter threshold of -32 dB to -21 dB for ice-free water in the lakes studied through the TSX image, although, for Sentinel-1, there was a range from -18 dB to -15 dB for ice-free water in the lakes. The TSX image is the most suitable for monitoring lake phenology, due to its spatial resolution, while the S-1 is limited to lakes of more than 10.000 m². It is recommended to consider meteorological conditions, especially wind, snow precipitation, and temperature changes, which represent significant changes in the backscatter values. The methodological recommendations regarding the use of TSX and S-1 imagery can be used for mapping lake ice cover and monitoring both ice break-up events and lake surface melt in glacial and periglacial environments.